Stent Fracture after Everolimus-Eluting Stent Implantation - Ali S. Almasood; Xavier Freixa; Sohail Q. Khan; Peter H. Seidelin; Vladimír Džavík (Cardiology Research and Practice)
Compared with bare-metal stents, drug-eluting stents (DES) have greatly reduced the risk of in-stent restenosis (ISR) by inhibiting neointimal growth. Nevertheless, DES are still prone to device failure, which may lead to cardiac events. Recently, stent fracture (SF) has emerged as a potential mechanism of DES failure that is associated with ISR. Stent fracture is strongly related to stent type, and prior reports suggest that deployment of sirolimus eluting stents (SES) may be associated with a higher risk of SF compared to other DES. Everolimus eluting stents (EESs) represent a new generation of DES with promising results. The occurrence of SF with EES has not been well established. The present paper describes two cases of EES fracture associated with ISR.